Connections between settlement structure, land use and the process of gypsy segregation in Hajdúböszörmény - Mező, Barna (Acta Agraria Debreceniensis, 2010)
The main aim of this study is to explore the connections between the unique settlement structure circumstances of Hajdúböszörmény and the social problams related to the gypsy minority. After the change of regime, the gypsy population increased especially quickly in some parts of the city, which is in connection with the settlement network position and the internal division of the settlement. The significant segregation of the gypsy minority appeared as a new phenomenon in the city, whose reason was the increasing migration of gypsies from Northeastern Hungary and the relatively low price of the abandoned real estates located in the outskirts and external settlement parts of the city. Even the gypsy population living in the city for a long time separates itself from the immigrant groups that live in run down houses and practicle have no connection with the job market of the city. It is the typical rural segregation process known only in small village regions (e.g. Southern Baranya, Cserehát) that now goes on in the outskirts of Hajdúböszörmény.